The road to reform Pakatan Rakyat in Selangor - Yeoh, Tricia (Strategic Information and Research Development Centre, 2010)
Malaysia's general election of 2008 handed, amongst its many shocks, control of Malaysia's most prosperous state to the opposition. In this assessment various contributors examine the early impact of the change in the state's politics, economics, society and culture as well as discussing the difficulties of delivering the state government's ambitious plans